Strategi Pembelajaran Pendidikan Agama Hindu Dalam Membentuk Karakter Siswa - Ni Kadek Kristina Dewi; I Ketut Sudarsana (Cetta: Jurnal Ilmu Pendidikan, 2018)
Hinduism Education can be started from an early age through the family path, in this case the child is given a training and learning every day by his parents. After increasing age should be given knowledge related to self-relationship with God. Humans with each other and human relations with nature so that there is a harmonious relationship between each other. Education is a very important basis in building human character but nowadays education loses its true meaning, the assessment is based on the many graduates of schools and scholars with high degrees who have immoral behavior, so in this case a Hindu religious education learning strategy is needed which is a learning plan in designing teaching materials based on the Vedic holy library.